If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1(3x + 6) = 5x + -47 Reorder the terms: 7x + -1(6 + 3x) = 5x + -47 7x + (6 * -1 + 3x * -1) = 5x + -47 7x + (-6 + -3x) = 5x + -47 Reorder the terms: -6 + 7x + -3x = 5x + -47 Combine like terms: 7x + -3x = 4x -6 + 4x = 5x + -47 Reorder the terms: -6 + 4x = -47 + 5x Solving -6 + 4x = -47 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -6 + 4x + -5x = -47 + 5x + -5x Combine like terms: 4x + -5x = -1x -6 + -1x = -47 + 5x + -5x Combine like terms: 5x + -5x = 0 -6 + -1x = -47 + 0 -6 + -1x = -47 Add '6' to each side of the equation. -6 + 6 + -1x = -47 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = -47 + 6 -1x = -47 + 6 Combine like terms: -47 + 6 = -41 -1x = -41 Divide each side by '-1'. x = 41 Simplifying x = 41
| 5x^2+1=2x | | 2y^3-7y^2+3=0 | | 50x^2+1=2x | | 6x-7x-5=0 | | 16x-282=6x-12 | | 52-6x=12x+18 | | 9x-(7x+2)=3x-22 | | 6x+22=16x-98 | | 3x^2+2x-40=0 | | 3x^2+58x-40=0 | | 3x^2+119x-40=0 | | x^2+25x-24=0 | | 2x+125=6x+93 | | (x)(x+1)(x+2)=720 | | 2x+25=6x+93 | | 3x^2-29x-10=0 | | x^4-4x^2+12x+9= | | x^4-4x^2+12x+9=0 | | 3x+2.3=5x+1.7 | | (3x-2)(x^2-6x+1)=0 | | a*12=b | | 5x+15=70 | | 4x^2-300=0 | | X+y=3x-5 | | 8x-7=7x-5 | | 8x=16.8 | | 7x=24.5 | | 3.4x=17 | | x^2+23=10x | | 4(2x-1)=3 | | 5x+2(1-3x)=6(x+5) | | 4x-8=3x+1 |